Informal Financial Practices and Entrepreneurial Growth: A Qualitative Study of Small Business Owners in Makassar, Indonesia - Andi Mustika Amin (Abadi Institute, 2026)
This qualitative study investigates how informal financial practices shape the growth trajectories of micro and small enterprises in Makassar, Indonesia. Drawing on six months of ethnographic fieldwork, including participant observation and semi-structured interviews with 18 small business owners, the research examines three predominant forms of informal finance: rotating savings and credit associations (arisan), financing sourced from family and kinship networks, and the conduct of business through undocumented cash transactions. The Results reveal that these practices are not passive responses to exclusion from the formal financial sector but rather active, culturally grounded strategies that confer social agency, build economic resilience, and fulfill fundamental needs for belonging and security. Theoretically, the study contributes to the literature on the informal economy, behavioral finance, and social capital theory by demonstrating how trust, reciprocity, and community norms function as genuine economic infrastructure in contexts where formal institutions are either inaccessible or mistrusted. At the same time, the research identifies significant constraints embedded within these informal systems, particularly their tendency to limit business scalability, impede formalization, and reinforce existing social hierarchies. A comparative analysis situates Makassar within a broader Southeast Asian urban context alongside Jakarta, Manila, and Bangkok, revealing both shared drivers of informality and city-specific cultural adaptations. The study argues that effective financial inclusion strategies must engage with, rather than displace, existing social structures, and that policies designed to bridge formal and informal finance must be culturally sensitive and locally grounded.